An Up-to-Date Overview of Therapeutic Agents for the Treatment of COVID-19 Disease - Mulaw Belete T (Dove Medical Press, 2020)
Tafere Mulaw Belete Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tafere Mulaw Belete Tel +251 918045943Email mutafere@yahoo.comAbstract: Acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has a great potential to overwhelm the world healthcare systems that may lead to high morbidity and mortality. It also affects world economic development in the future. Currently, no proven effective drugs or vaccines are available for the management of COVID-19 disease. The pace of normal drug development progression is unacceptable in the context of the current pandemic. Therefore, repurposing the existing drugs that were used for the treatment of malaria, Ebola, and influenza helps rapid drug development for COVID-19. Currently, several repurposing candidate drugs are in a clinical trial including, chloroquine monoclonal antibodies, convalescent plasma, interferon, and antiviral therapies. Antiviral drugs like arbidol, remdesiv and favirnavir are the most promising due to the similarities of the viruses regarding viral entry, fusion, uncoating, and replication. This review article provides an overview of the potential therapeutic agent, which displayed better clinical treatment outcomes. Moreover, with further understanding of the SARS-CoV-2 virus, new drugs targeting specific SARS-CoV-2 viral components arise, and investigations on these novels anti-SARSCoV- 2 agents are also reviewed.Keywords: corona virus, SARS-CoV-2, SARS-CoV, COVID-19, chloroquine